Comparison of thermal modeling, microstructural analysis, and Ti‐in‐quartz thermobarometry to constrain the thermal history of a cooling pluton during deformation in the Mount Abbot Quadrangle, CA. (30th March 2017) - Nevitt, Johanna M.; Warren, Jessica M.; Kidder, Steven; Pollard, David D.
Abstract: Granitic plutons commonly preserve evidence for jointing, faulting, and ductile fabric development during cooling. Constraining the spatial variation and temporal evolution of temperature during this deformation could facilitate an integrated analysis of heterogeneous deformation over multiple length‐scales through time. Here, we constrain the evolving temperature of the Lake Edison granodiorite within the Mount Abbot Quadrangle (central Sierra Nevada, CA) during late Cretaceous deformation by combining microstructural analysis, titanium‐in‐quartz thermobarometry (TitaniQ), and thermal modeling. Microstructural and TitaniQ analyses were applied to 12 samples collected throughout the pluton, representative of either the penetrative "regional" fabric or the locally strong "fault‐related" fabric. Overprinting textures and mineral assemblages indicate the temperature decreased from 400–500°C to <350°C during faulting. TitaniQ reveals consistently lower Ti concentrations for partially reset fault‐related fabrics (average: 12 ± 4 ppm) than for regional fabrics (average: 31 ± 12 ppm), suggesting fault‐related fabrics developed later, following a period of pluton cooling. Uncertainties, particularly in TiO2 activity, significantly limit further quantitative thermal estimates using TitaniQ. In addition, we present a 1‐D heat conduction model that suggests average pluton temperature decreased from 585°C at 85 Ma to 332°C at 79 Ma, consistent with radiometric age data for the field. Integrated with the model results, microstructural temperature constraints suggest faulting initiated by ∼83 Ma, when the temperature was nearly uniform across the pluton. Thus, spatially heterogeneous deformation cannot be attributed to a persistent temperature gradient, but may be related to regional structures that develop in cooling plutons. Key Points: Joints, ductile shear zones, and faults formed in a cooling granodiorite pluton and preserve overprinting microstructures Synthesis of thermal model with microstructural data reveals timing of and potential relationships between structural events Uncertainty in TiO2 activity and partial reequilibration during recrystallization limit utility of titanium‐in‐quartz thermobarometer